A Pediatric Strategy for the Next Phase of the SARS–CoV-2 Pandemic - Buonsenso, Danilo; Valentini, Piero; Moscato, Umberto; Ricciardi, Walter; Roland, Damian (Frontiers in Pediatrics, 2020)
Although the first wave of the SARS-CoV-2 pandemic relatively spared children, the next winter season will put a strain on health systems including paediatric services. Staff managing children will need to deal not only with suspected cases of COVID-19, but also with the classic infectious agents that involve children during cold seasons. It will be necessary for physicians, institutions, policy makers, families, to prepare themselves for difficulties of this phase of the pandemic. Otherwise the same problems experienced during the first wave of SARS-CoV-2, including shortages of human resources, PPEs and uncertainty will be exacerbated by significant issues in hospital capacity. We highlight the potential role of improved vaccination services, school reorganization, home-outpatient-inpatients flows and telemedicine services in order to face the coming winter season.